(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is an attempt to study the definition of the term «artistic image» within the scope of linguopoetics. Brief information is given on the development of this science, its main categories and parameters, and the content of the term of literary image is presented, based on the relationship between the methods and methods of scientists from various branches of philological sciences. Also presented is a description of the images of characters in the works of Ch. Aitmatov.